C-Reactive Protein and Incident Hypertension in Black and White Americans in the REasons for Geographic And Racial Differences in Stroke (REGARDS) Cohort Study. (16th December 2020) - Plante, Timothy B; Long, D Leann; Guo, Boyi; Howard, George; Carson, April P; Howard, Virginia J; Judd, Suzanne E; Jenny, Nancy Swords; Zakai, Neil A; Cushman, Mary
Abstract: Background: More inflammation is associated with greater risk incident hypertension, and Black United States (US) adults have excess burden of hypertension. We investigated whether increased inflammation as quantified by higher C-reactive protein (CRP) explains the excess incidence in hypertension experienced by Black US adults. Methods: We included 6, 548 Black and White REasons for Geographic and Racial Differences in Stroke (REGARDS) participants without hypertension at baseline (2003–2007) who attended a second visit (2013–2016). Sex-stratified risk ratios (RRs) for incident hypertension at the second exam in Black compared to White individuals were estimated using Poisson regression adjusted for groups of factors known to partially explain the Black–White differences in incident hypertension. We calculated the percent mediation by CRP of the racial difference in hypertension. Results: Baseline CRP was higher in Black participants. The Black–White RR for incident hypertension in the minimally adjusted model was 1.33 (95% confidence interval 1.22, 1.44) for males and 1.15 (1.04, 1.27) for females. CRP mediated 6.6% (95% confidence interval 2.7, 11.3%) of this association in females and 19.7% (9.8, 33.2%) in males. In females, CRP no longer mediated the Black–White RR in a model including waist circumference and body mass index, while in males the Black–White difference was fully attenuated in models including income, education and dietary patterns. Conclusions: Elevated CRP attenuated a portion of the unadjusted excess risk of hypertension in Black adults, but this excess risk was attenuated when controlling for measures of obesity in females and diet and socioeconomic factors in males. Inflammation related to these risk factors might explain part of the Black–White disparity in hypertension.